COVID-19 and the related accounting considerations in preparing financial statements and disclosure requirements. - Ghias Khan (Institute of Business Management, 2020)
The purpose of this case study is to examine the impacts of COVID-19 on financial reporting from the different view sides of IFRS disclosure requirements. Most of the countries in the world carrying the effects of COVID-19 and nearly a quarter of the population is quarantined and most of the business is in lockdown condition. As a result of the businesses working online as well as change their pattern of operations due to COVID-19 pandemic. The government also imposes legislation related to it and there must be significant changes in IFRS implication concerning pandemic to improve the situation in all the way. A questionnaire has been prepared and send to the concerned officials of the company in the subject here to ascertain the facts related to the implications of IFRS adoption in the current period of the pandemic. The questionnaire covers around 31 aspects related to disclosures as per IFRS and the study here analyzes how Unilever Pakistan Limited adopted these changes or in which areas still following the same policy without impacting COVID-19.